Effects of Processing Parameters on Properties of Activated Carbon from Palm Shell: Sodium Hydroxide Impregnation - Sathaporn Bhungthong (Science Faculty of Chiang Mai University, 2019)
The preparation and properties of activated carbons (ACs) produced from palm shells using sodium hydroxide (NaOH) as an activating reagent were studied. The influences of processing parameters: activation temperature (500-1000°C), impregnation ratio (1-3) and activation duration (1-3 h), on the properties of the prepared ACs were investigated. These properties included pore development, Brunauer-Emmett-Teller (BET) surface area, yield, iodine number, methylene blue (MB) adsorption, composition, and surface chemistry and morphology. The optimum conditions for activation were NaOH/char ratio of 2:1 at a temperature of 900°C for duration of 2 h. Under these conditions, ACs with maximum BET surface area of 2363 m2 g-1 was obtained, with iodine number and MB adsorption of 1389 mg g-1 and 55% respectively. Experimental results showed that it was feasible to produce ACs with a high BET surface area and high adsorption capability from palm shells.